2018
DOI: 10.1038/s41467-018-05982-z
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-mediated mesenchymal transformation renders endothelial resistance to anti-VEGF treatment in glioblastoma

Abstract: Angiogenesis is a hallmark of cancer. However, most malignant solid tumors exhibit robust resistance to current anti-angiogenic therapies that primarily target VEGF pathways. Here we report that endothelial-mesenchymal transformation induces glioblastoma (GBM) resistance to anti-angiogenic therapy by downregulating VEGFR-2 expression in tumor-associated endothelial cells (ECs). We show that VEGFR-2 expression is markedly reduced in human and mouse GBM ECs. Transcriptome analysis verifies reduced VEGFR-2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 64 publications
1
101
0
Order By: Relevance
“…Western blotting assay of COX-2, iNOS and VEGF did not totally prove the anti-angiogenesis function of AVNP2 on gliomas but gave us a hint, which needs to be investigated deeper by means of ELISA and the tubule formation test in vivo and in vitro (Chen et al, 2016). The activation or suppression of endothelial cells (ECs), which play an important part in tumour angiogenesis, are worthy of study and discussion too (Liu et al, 2018). In our experiment, results corresponded to the inflammation-related proteins mentioned before.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting assay of COX-2, iNOS and VEGF did not totally prove the anti-angiogenesis function of AVNP2 on gliomas but gave us a hint, which needs to be investigated deeper by means of ELISA and the tubule formation test in vivo and in vitro (Chen et al, 2016). The activation or suppression of endothelial cells (ECs), which play an important part in tumour angiogenesis, are worthy of study and discussion too (Liu et al, 2018). In our experiment, results corresponded to the inflammation-related proteins mentioned before.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Bhat et al found that PN GSCs transformed to the MES state through the NF-κB pathway, with an elevated expression of CD44 and radioresistant phenotypes 37 . Thereafter, several studies were conducted to elucidate the potential mechanisms of how gliomas acquire the MES-signature through activating NF-κB transcriptional programs [38][39][40][41] . Furthermore, therapeutic approaches targeting the NF-κB pathway in GBM have (see figure on previous page) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given their localization and protumor behavior, TAMs have been suggested to promote resistance to antiangiogenic agents, such as bevacizumab, but the underlying mechanisms remain unknown (29)(30)(31). Evidence suggests that resistance may be due to changes in the tumor microenvironment and the presence of myeloid-derived TAMs (32,33). Mechanisms of TAM infiltration may include passive migration due to a leaky BBB or active migration via chemokine gradients; however, which of these mechanisms is most responsible remains unclear.…”
Section: Two-photon Imaging Permits Direct Longitudinal Observation Ofmentioning
confidence: 99%